2006
DOI: 10.1248/cpb.54.275
|View full text |Cite
|
Sign up to set email alerts
|

Two Phenylpropanoid Glycosides from Neopicrorhiza scrophulariiflora

Abstract: Neopicrorhiza scrophulariiflora (PENNELL) HONG (basionym. Picrorhiza scrophulariiflora PENNELL) is distributed throughout the high altitude (Ͼ4400 m) regions in southeastern Tibet and the northwestern Yunnan Province of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Its molecular formula was determined to be C 28 3 The relatively large J value (6.9 Hz) of the anomeric proton (d 4.94) of glucose indicated that the anomeric configuration was b. The point of linkage of two sinapoyl moieties with the glucose was solved by analysis of the HMBC experiment, in which the cross peaks between H-1 0 (d 4.94) and C-4 (d 136.0), H-6 0 (d 4.25 and 4.17) and C-9 00 (d 166.6) were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Its molecular formula was determined to be C 28 3 The relatively large J value (6.9 Hz) of the anomeric proton (d 4.94) of glucose indicated that the anomeric configuration was b. The point of linkage of two sinapoyl moieties with the glucose was solved by analysis of the HMBC experiment, in which the cross peaks between H-1 0 (d 4.94) and C-4 (d 136.0), H-6 0 (d 4.25 and 4.17) and C-9 00 (d 166.6) were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, there has been no detailed research on the extraction procedures for these chemical constituents. Generally, the crude extracts wer prepared with different concentrations of methanol, ethanol or acetone-water solution by the impregnation method, refluxing extraction or decoction method [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…The 27 monosaccharide [16,18,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35] esters 1 – 10 , 21 – 27 represent the simplest structures found among CASEDs (Figure 1, Figure 2, Figure 3, Figure 4 and Figure 5). The main structural moiety of these compounds (Figure 2 and Figure 5), is a β- d -glucose ester, or an α- l -rhamnose ester in compounds 11 – 15 (Figure 3).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…In Nepal, a number of ethnobotanical uses of its unprocessed rhizomes have well been documented to treat common cold, fever, sinusitis, headache, diarrhea, paralysis, hysteria, anemia, high blood pressure, sore throat, gastritis, intestinal pains, snake and scorpion sting, abdominal pain, indigestion, liver troubles, bile disorders, continuous pain in the chest and heart, increased heartbeat, difficulty in breathing, jaundice, cuts, wounds, and conjunctivitis [ 10 – 18 ]. Chemical constituents of rhizomes of Neopicrorhiza are well studied which comprise iridoid glycosides [ 19 21 ], triterpenoids [ 22 ], phenolic glycosides [ 23 ], phenylethanoid glycosides [ 24 ], cucurbitacin glycoside [ 25 , 26 ], and phenylpropanoid glycosides [ 27 ] having a wide range of biological activities.…”
Section: Introductionmentioning
confidence: 99%